Recovery Of Nickel From Simulated Nickel Bath Solutions On Carbon Matrices Using An Electrogenerative Process - Poh , Wan Hui (2010)
Nickel plating is used extensively for decorative, engineering and electroforming purposes. The most widely used method of removing nickel from effluents is to precipitate nickel and other metals as hydroxides or sulfides. A batch electrochemical reactor operating in an electrogenerative mode was used to recover nickel from simulated nickel bath solutions. A spontaneous chemical reaction will take place in the reactor and generate an external flow of current. In this present work, a batch cell with an improved design using three-dimensional cathodes namely porous graphite and reticulated vitreous carbon (RVC) is used.